A new species and new records of Cercophora from argentina - Catania, M.D.V. (2011)
Three species of Cercophora were found during a survey of the biodiversity of microfungi in northwest Argentina. Cercophora argentina possesses a unique combination of morphological characters and is described as a new species, while C. costaricensis and C. solaris are reported as new records for Argentina. Other species of Cercophora known from this region include C. natalita and C. coprogena, which is fully illustrated for the first time and determined herein to be a synonym of C. californica. All other species are described and illustrated. © 2011 by The Mycological Society of America.